Survey on De-Duplication Techniques at Public Cloud - Sajjan, Rajani; Chavan, Gayatri; Vijay R, Ghorpade (International Journal of Computer Sciences and Engineering, 2025)
Since the demand for data storage is increasing day by day and by the industry analysis we can say that digital data is increasing gradually, but the storage of redundant data is excess which results in most of the storage used unnecessary to keep identical copies. So this survey paper introduces various de-duplication techniques to efficiently utilize the cloud storage system.